[tex]\displaystyle\sum_{n=1}^\infty(-1)^{n-1}\tan^{2n}\theta=1-\sum_{n=0}^\infty(-\tan^2\theta)^n=1-\dfrac1{1+\tan^2\theta}[/tex]
where [tex]|-\tan^2\theta|=\tan^2\theta<1[/tex] in order that the series converges, which is to say the series converges for
[tex]\tan^2\theta<1\implies|\tan\theta|<1\implies|\theta|<\dfrac\pi4[/tex]
We can simplify the sum a bit further, noting that [tex]1+\tan^2\theta=\sec^2\theta[/tex], giving
[tex]\displaystyle\sum_{n=1}^\infty(-1)^{n-1}\tan^{2n}\theta=1-\cos^2\theta=\sin^2\theta[/tex]